Ecological Ambivalence, Complexity, and Change Perspectives from the Environmental Humanities. - Müller, Simone M.; Schmidt, Matthias; Twelbeck, Kirsten, 1965- (Oxford : Taylor & Francis Group, 2025)
This book provides a systematic, interdisciplinary analysis of the conflicts, issues and tensions associated with today's ecological transformation processes from an environmental humanities perspective. Of interest to researchers, academics and students studying environmental humanities, the social sciences and environment sciences.
Wealth, Health, Production, Consumption, Waste, and Destruction: Connecting the Dots -- Decoupling Wealth From Waste Production: The Circular Economy -- Decoupling the Good Life From Production and Consumption: Degrowth -- Conclusion -- Notes -- 8 Farming the Wind: Aeolian Politics and the Sacred Desertscapes (Orans) of Rajasthan -- Introduction -- The Politics of (Renewable) Energy in Postcolonial India: Ambivalences, Ambiguities, and Tensions -- Revitalizing Orans: Challenging Coloniality Through Interrogating Wasteland Narratives
Description based upon print version of record.
Reclaiming Aalaji Ka Oran in Jaisalmer: Recognizing Local Tensions Amidst Global Concerns
Keywords: Human ecology; Ecology